2007
DOI: 10.1007/s00484-007-0098-3
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic conditions of lactating Friesian cows during the hot season in the Po valley. 1. Blood indicators of heat stress

Abstract: In two consecutive summers, 21 and 18 cows, respectively, were monitored for blood parameters and milk yield, to assess their variation according to the level of heat stress at different stages of lactation. During both years, the cows were monitored according to their lactation phase (early, mid-, and late) at the beginning of the summer. Climatic conditions were described through the temperature humidity index. Cows were monitored for breathing rate, rectal temperature, blood metabolites and enzymes, and mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
80
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(93 citation statements)
references
References 18 publications
11
80
2
Order By: Relevance
“…The change may be due to decreased liver activity and increased lipolysis in peripheral tissues . Increased skeletal muscle breakdown was established, as indicated by the increase in plasma creatinine concentration, and was also reported by Abeni et al (2007) and Schneider et al (1988). The effect of hot summer conditions on lipolysis and amino acid breakdown was not reduced by access to shade, however.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…The change may be due to decreased liver activity and increased lipolysis in peripheral tissues . Increased skeletal muscle breakdown was established, as indicated by the increase in plasma creatinine concentration, and was also reported by Abeni et al (2007) and Schneider et al (1988). The effect of hot summer conditions on lipolysis and amino acid breakdown was not reduced by access to shade, however.…”
Section: Discussionsupporting
confidence: 69%
“…◊ Blood plasma (Cl − ) and (ALP) are not significantly influenced by HLI for animals with access to shade (Table 3). Abeni et al (2007) also found a decrease in blood plasma urea concentrations during two hot periods under Italian summer conditions. In cattle, plasma and milk urea concentrations are very much determined by the rumen degradable protein balance: a largely positive balance leads to higher NH 3 production in the rumen, which results in higher urea concentrations in blood and milk.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…In addition, the cholesterol and triglyceride levels in blood plasma also decline. These phenomena may be caused by an increase in the mobilization of fat in the peripheral tissue (Abeni et al, 2007). As a methyl donor, betaine has the role of promoting fatty acid oxidation (Davidson et al, 2008).…”
Section: Dietary Betaine Supplementation In Dairy Cowsmentioning
confidence: 99%